Embolization of a peripheral cerebral aneurysm associated with intracranial major artery occlusion through a transdural anastomotic artery: Case report. Issue 2 (April 2019) - Fukuda, Norito; Kanemaru, Kazuya; Hashimoto, Koji; Yoshioka, Hideyuki; Senbokuya, Nobuo; Yagi, Takashi; Kinouchi, Hiroyuki
A peripheral cerebral aneurysm is known to develop at collateral vessels as a result of hemodynamic stress by the occlusion of the intracranial major arteries. We report a case of successful embolization of a ruptured aneurysm through a transdural anastomotic artery. The aneurysm formed at the developed collateral vessel from the meningeal branch of the occipital artery (OA) to the posterior pericallosal artery. A 59-year-old man presented with acute-onset headache, and computed tomography revealed subarachnoid hemorrhage and intracerebral hemorrhage at the splenium of the corpus callosum with intraventricular hemorrhage. Digital subtraction angiography demonstrated a ruptured aneurysm located at a transdural anastomotic artery from the right OA to the posterior pericallosal artery. The patient underwent endovascular treatment for the aneurysm through the transdural anastomotic artery with a coil and n-butyl-2-cyanoacrylate. Because it was impossible to navigate a microcatheter to the aneurysm through the right anterior cerebral artery because of the occlusion of its proximal portion, it was advanced through the transdural anastomosis from the right OA. The aneurysm was completely occluded without complications. Endovascular embolization is a useful treatment option for a peripheral cerebral aneurysm developed at a collateral vessel with intracranial major artery occlusion.